Singing Accent Americanisation in the Light of Frequency Effects: LOT Unrounding and PRICE Monophthongisation in Focus - Konert-Panek, Monika (Research in Language, 2018)
The paper investigates – within the framework of usage-based phonology – the significance of lexical frequency effects in singing accent Americanisation. The accent of Joe Elliott of a British band, Def Leppard is analysed with regard to LOT unrounding and PRICE monophthongisation. Both auditory and acoustic methods are employed; PRAAT is used to provide acoustic verification of the auditory analysis whenever isolated vocal tracks are available. The statistical significance of the obtained results is verified by means of a chisquare test. In both analysed cases the percentage of frequent words undergoing the change is higher compared with infrequent ones and in the case of PRICE monphthongisation the result is statistically significant, which suggests that word frequency may affect singing style variation.